Antiphospholipid antibodies and autoimmune haemolytic anaemia - Ames, Paul R.J. (2020)
The relationship between antiphospholipid antibodies (aPL) and autoimmune haemolytic anaemia (AIHA) has never been systematically addressed. The aim of this study is to assess the link between aPL and AIHA in adult systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS). This study performed an EMBASE/PubMed search from inception to June 2019 and meta-analysis using Peto’s odds ratios. The pooled prevalence (PP) of IgG/IgM anticardiolipin (aCL) and lupus anticoagulant (LA) was greater in AIHA +ve than AIHA –ve patients (34.7% vs. 27.6%, p = 0.03; 33.3% vs. 21.8%, p < 0.0001; 20.9% vs. 8.3%, p = 0.01). The PP of AIHA was greater in: (1) IgG and IgM aCL +ve than-ve patients (21.8% vs. 11.1%, p = 0.001 and 18.7% vs. 6.3%, p < 0.0001), (2) in SLE related APS than in primary APS patients (22.8% vs. 3.9% p < 0.0001), (3) in APS +ve than APS-ve SLE patients (23.2% vs. 8.4%, p = 0.01), and (4) in thrombotic APS than non-thrombotic APS/SLE patients (26.8% vs. 10%, p = 0.03). The PP of IgG/IgM aCL and LA was greater in DAT +ve than DAT-ve patients (42.4% vs. 12.8%, p < 0.0001; 26.2% vs. 12.8%, p = 0.03 and 29.2% vs. 15.7%, p = 0.004 respectively). It was found that AIHA prevalence is maximal in SLE with aPL/APS, low-moderate in SLE without aPL and minimal in PAPS. Moreover, AIHA is rightly included among the classification criteria for SLE but not for APS/aPL. The significance of an isolated DAT positivity remains unclear in this setting.